Characterization of Secondary Metabolite Compounds from Ethyl Acetate Extract of Japanese Papaya Leaves (Cnidoscolus Aconitifolius) - VIta Montolalu; Rymond Rumampuk; Emma Pongoh (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Indonesia has abundant biodiversity and great potential as a source for the development of natural organic chemical compounds. One plant that is widely used traditionally is Japanese papaya (Cnidoscolus aconitifolius), which is known to have potential as a source of natural chemical compounds because it contains various secondary metabolites with pharmacological activities. This study aims to isolate and identify secondary metabolites from the ethyl acetate fraction of Japanese papaya leaves. Isolation was carried out using the maceration method, and separation and purification were done using gravity column chromatography and thin layer chromatography. The identification of compound structures was carried out using Proton Nuclear Magnetic Resonance (¹H-NMR) and Carbon-13 Nuclear Magnetic Resonance (¹³C-NMR) spectroscopy. The analysis results showed that the obtained isolate is suspected to be a compound in the flavanone group, namely 3',4',5-trihydroxyflavanone.